2019
DOI: 10.1039/c9ra05629g
|View full text |Cite
|
Sign up to set email alerts
|

SF6 abatement in a packed bed plasma reactor: study towards the effect of O2 concentration

Abstract: SF6 is a greenhouse gas with extremely high global warming potential (GWP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…It can absorb free electrons in the ambient, which will weaken collision and decomposition. References [13] and [37] also reported the similar conclusion that the highest removal efficiency has been obtained under an optimized amount of oxygen condition. However, the oxygen concentrations were not same in the two pieces of research, which may be due to the difference between their working conditions.…”
Section: Measurementsupporting
confidence: 54%
“…It can absorb free electrons in the ambient, which will weaken collision and decomposition. References [13] and [37] also reported the similar conclusion that the highest removal efficiency has been obtained under an optimized amount of oxygen condition. However, the oxygen concentrations were not same in the two pieces of research, which may be due to the difference between their working conditions.…”
Section: Measurementsupporting
confidence: 54%
“…Electrons absorb energy from an electric field and transfer it to plasma components, resulting in ionization, which is important for degrading contaminants ( Benedikt, 2010 ; Sanito et al., 2020 , 2022a ). High energy electrons can be generated from the metastable argon’s atoms ( Tian et al., 2019 ). The kinetic energy of free electrons causes the high free electrons that creates excite argon ( Zhang et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…[19] Furthermore, Zhang et al found that SF 6 can be decomposed more effectively in a packed-bed reactor compared with the DBD reactor, therefore, they explored the effect of the type and the size of the packing materials on SF 6 degradation. [21,26,27] They achieved 88.6% SF 6 degradation efficiency and 17.1 g/kWh energy yield in a packed-bed reactor with the packing material of glass beads. [21] In the present work, a nanosecond pulsed power supply is employed to excite PBD plasma instead of a traditional AC power supply, and the key F I G U R E 11 The three-dimensional response surface plots of the interaction of pulsed voltage, gas flow rate, oxygen content, and relative humidity on degradation efficiency.…”
Section: Comparison Of the Present Work With Other Literaturementioning
confidence: 99%
“…The added active gases, including H 2 O and O 2 , have been used to improve the plasma activity, because plenty of O and ·OH produced are considered crucial in the decomposition of the contaminants. [ 26 ] Therefore, it is necessary to study the effect of the process parameters on the degradation of SF 6 in detail.…”
Section: Introductionmentioning
confidence: 99%